Young marriage, parenthood and divorce in Zambia - Mweemba, O; Mann, G (Young Lives, 2020)
Zambian law prohibits marriage under 21 but the practise, driven by circumstance, stubbornly persists, albeit increasingly as informal cohabitations which are inseparable from pregnancy and parenthood. For many adolescents, who lack the experience, emotional maturity and financial resources to cope, they are a complex and challenging experience, rarely investigated until now.